Federalism and the tug of war within - Ryan, Erin. (New York : Oxford University Press, 2011)
As environmental, national security, and technological challenges push American law into ever more inter-jurisdictional territory, this book proposes a model of 'Balanced Federalism' that mediates between competing federalism values and provides greater guidance for regulatory decision-making.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Federal government -- United States